2010
DOI: 10.3109/08037051.2010.484158
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde-modified low-density lipoproteins as biomarker for atherosclerosis

Abstract: MDA-modified LDL estimation has a diagnostic accuracy and may be used as an independent biochemical marker for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 11 publications
1
13
0
6
Order By: Relevance
“…114 Malondialdehyde-modified oxidized low-density lipoproteins (oxLDL) are implicated in CVD in general, 115 and especially in SLE-associated CVD. 114 HDL, but not oxHDL, protects against the atherogenic effects of oxLDL.…”
Section: Oxidative Stress and T-cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Malondialdehyde-modified oxidized low-density lipoproteins (oxLDL) are implicated in CVD in general, 115 and especially in SLE-associated CVD. 114 HDL, but not oxHDL, protects against the atherogenic effects of oxLDL.…”
Section: Oxidative Stress and T-cell Dysfunctionmentioning
confidence: 99%
“…119 As mentioned in the section on comorbidities, oxHDL is associated with atherosclerosis in SLE, 100 and oxLDL is a biomarker of CVD. 115 …”
Section: Clinical Approaches and Implicationsmentioning
confidence: 99%
“…Some cross-sectional studies have shown a significant correlation between serum levels of MDA-LDL and LDL-C 34, 35 and coronary endothelial function. 36 In the present study, we also found that the MDA-LDL/ LDL-C ratio increased in the ezetimibe addition group despite the lack of significant reductions in serum LDL-C and MDA-LDL, and the ratio did not change with increasing the dose of atorvastatin.…”
Section: -31mentioning
confidence: 99%
“…The polyunsaturated fatty acids in cholesteryl esters, phospholipids and triglycerides are also subjected to free radical-initiated oxidation to yield a broad array of smaller fragments (Matsuura et al, 2008). This results in a variety of reactive aldehyde products, including (E)-4-hydroxynon-2-enal (HNE) and malondialdehyde (MDA), which form covalent adducts with amino acid residues of LDL, generating HNE-LDL and MDA-LDL, respectively (Annangudi et al, 2008;Viigimaa et al, 2010). Glycated LDL is formed by the nonenzymatic covalent binding of reactive aldehydes (from glucose or related species) to a reactive amine (e.g., lysine and arginine side chains) on apoB-100 (Brown et al, 2007).…”
Section: Ldl and Its Modified Formsmentioning
confidence: 99%